PENGARUH PARTISIPASI ANGGARAN, SELF ESTEEM DAN BUDGET EMPHASIS TERHADAP BUDGETARY SLACK PADA HOTEL BERBINTANG DI DENPASAR - Karma Resen, Nyoman Sancita (E-Jurnal Akuntansi, 2015)
This research attempts to find the effect of budget participation, self esteem, and budget emphasis on budgetary slack in star hotels in Denpasar. In order to reach the purpose of this research, purposive sampling method was chosen with 23 hotels and 35 participants all of whom are middle level managers participating in budget making. The research is conducted by using multiple linear regression as an analytical technique in order to obtain the answer for the research questions. Budget is a planning and controling tool used to obtain the organization’s goals. Budget participation, self esteem and budget emphasis can lead to the creation of budgetary slack. This is due to the reason that in budget participation, subordinates can use their creativity in the process of preparing the budget. Self esteem in budget participation can lead to budgetary slack as well, this is due to the great influence given of self esteem on every action conducted by individual including their behaviour in the process of preparing the budget. Budget emphasis can also lead to budgetary slack. If the subordinates believe that punishment and reward given by their superiors is determined by their performances, they will try build slack in preparing the budget. This research concludes that budget participation, self esteem, and budget emphasis have significant effect on budgetary slack in star hotels in Denpasar.
Keywords: Budget Participation, Self Eesteem; Budget Emphasis; Budgetary Slack